PENGENDALIAN WAKTU DENGAN METODE EARNED VALUE PADA PROYEK PEMBANGUNAN HOTEL FAVE KOTABARU YOGYAKARTA - Abma, Vendie (Teknisia, 2017)
All construction project require of cost and time control. Controlling of time the most important in the construction implementation so that the project can be in accordance with the time schedule. Controlling of time can be done byconsidering the project implementation performance. Project implementation can be late, faster, or even on time in accordance with time schedule. One of the time controlling that are used in this research is earned value method to know the project performance in terms of time. Object of this research is Building Construction Project of Fave Kotabaru Hotel, Yogyakarta. The data in this research are time schedule, RAB, and weekly progress report to get the value of BCWP and BCWS. Controlling analysis by earned value method obtained the value of Schedule Variance (SV), Schedule Performance Index (SPI), predict the value of estimation to completeand estimation at comlpete (ETC and EAC). Analysis result base on time of Building Construction Project of Fave Kotabaru Hotel was predicted to become late. All value of Schedule Variance (SV) from week 25 until 28 is negative (-) and the average value of Schedule Performance Index (SPI) at 7th month from week 25-28 is 0,63 (<1). The results mean that the time performance of the construction project is slower than the time schedule. Based on the performance at the 7th month observation, obtainedthe value of estimation to complete (ETC) the project is 20 weeks, then estimation at completion (EAC) is 48 weeks, 8 weeks slower than time schedule. The final result shows that the project was too late, so that it need to be re-schedule.